High-resolution fecal pharmacokinetic modeling in mice with orally administered antibiotics - Rie Maskawa; Lena Takayasu; Hideki Takayasu; Keiji Watanabe; Shusuke Takemine; Takashi Kakimoto; Kozue Takeshita; Seiko Narushima; Wataru Suda; Misako Takayasu (Scientific Reports)
Abstract High-resolution fecal pharmacokinetics are crucial for optimizing therapeutic design and evaluating gastrointestinal motility. However, empirical studies with detailed fecal concentration over time data remain limited. This study aims to characterize fecal pharmacokinetics through high-frequency sampling and parallelized fecal concentration quantification, establishing a simple pharmacokinetics model with physiologically interpretable parameters. We quantified vancomycin concentrations in fecal samples collected at a minimum interval of 4 hours from C57BL/6N mice following a single oral administration of either a low (1 mg/mL) or high (20 mg/mL) dose. Fecal concentrations gradually increased and exhibited an exponential decay, leading to the development of a compartmental model with an absorption phase. This simple model accurately fit the experimental data and provided physiological explanations for intra- and inter-individual pharmacokinetics variability. The results suggest that inter-individual differences in pharmacokinetics are attributable to fecal elimination capacity, which may be influenced by drug dosage via changes in gastrointestinal motility. Since the model predicts antibiotic concentrations within the gastrointestinal tract, it can be applied to fundamental studies investigating the effects of antibiotics on the gut microbiome and gastrointestinal motility.